Personal Variable Relationship of Cancer Patients in Thailand Using Log-linear Models - Yimprayoon, Pornpis; Ruktamatakul, Sittipong (Journal of Food Health and Bioenvironmental Science, 2018)
In this study, data sets of new cancer patients are used who were admitted between January 2012 and December 2013 at the National Cancer Institute Thailand. The main objective of this study is to test association between personal and cancer related variables using log-linear models. A test of independence is used to find the relationships between any two variables by chi-square tested and Cramer’s V. The results in this study display that most paired variables of personal and cancer/ clinical variables are significantly related at p-value < 0.01. For both male and female patients, the variable site of cancer is highly related to the stage of diagnosis, which provides the highest Cramer’s V value. Moreover, the two-dimensional log-linear models are used to find estimated parameters, expected frequencies and standardized residuals obtaining the best model for the relationships between two defined variables.